Interoperability and Trust Management Solutions for Establishing Secure Grids - Shashi (My University, 2012)
Security remains one of the fundamental challenges for adoption of Grid computing in a wider commercial context. Security challenges include finding suitable resources across the domains, irrespective of underlying platforms, leading to Interoperability challenges. Also in Grid computing scenario traditional assumptions for establishing and evaluating trust, do not hold good, there is an inherent need to establish trust between unknown players (service requesters, service providers, etc.). This leads to another type of security challenges, trust management challenges. The focus of this thesis is to address Interoperability and Trust Management challenges in Grids and provide solutions for these. As an outcome, three Interoperability Solutions: Thapar University eXtensible - INTEROperability System (TUX-INTERO), Thapar University eXtensible Interoperability Portal (TUX-INTEROP) and Pluggable, Interoperable and Extensible (PIE) have been proposed and developed. As Trust Management solution: Thapar University Extensible Trust management System (TUX-TMS) has been proposed and developed. TUX-INTERO is a Web Services based interoperability solution which discovers and integrates resources based on various platforms and middleware. TUX-INTEROP is a grid portal for secure interoperation of grids. PIE is grid portal which integrates resources from various middleware and allows access to end users at a single interface. TUX-TMS is a exible Reputation based Trust Management system which combines the merit of policy proof and reputation evaluation. TUX-INTERO and TUX-TMS have been integrated, deployed and tested on Thapar University Extensible-Collaborative Interoperability and Trust Management Solution (TUX-CITMS)- a Grid Testbed. This testbed spans across whole Thapar University Campus. Testing results have been presented in the form of numerous test cases. TUX- INTEROP and PIE have been deployed and tested further on Thapar University (TU) Campus Grid using a set of test cases. Every test case dedfines a testing criteria, test inputs, expected outputs and finally validates the outcome to be correct/ as expected. The results successfully exhibit interoperability between resources on multiple platforms and middleware. The testing results collectively demonstrate that the proposed solutions are working and can be effectively used to address interoperability and trust management challenges to establish secure Grids.
Ph.D Thesis
Keywords: Interoperability; Trust Management; Grid Computing; Grid Security